ANALYSIS OF THE DEVELOPMENT OF BMT AL BIRRY IN ENHANCING FINANCIAL INCLUSION IN PINRANG REGENCY - jabir, ulfa; Frihatni, Andi Ayu (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2025)
Baitul Maal wat Tamwil (BMT) is one of the Islamic financial institutions initiated by community participation to strengthen the local economy while also fulfilling social functions for public welfare. This study was motivated by the fact that BMT Al Birry aspires to contribute to the real sector but is still unable to compete effectively in the market. Customers also face issues such as delays in installment payments caused by declining turnover among financing recipients. Therefore, it is crucial to analyze how BMT Al Birry develops strategies to improve financial inclusion in Pinrang Regency.This research applies a qualitative case study approach, using observation, interviews, and documentation as data collection methods. Data analysis includes data reduction, presentation, and verification. The findings reveal that BMT Al Birry focuses on enhancing Islamic financial products and services such as musyarakah, mudharabah, murabahah, and qardhul hasan while actively promoting Islamic financial literacy and inclusive access. However, limited capital and competition from conventional banks remain significant challenges, prompting the need for improved service quality, stronger capital, and more effective literacy programs.